2016
DOI: 10.1051/matecconf/20163802004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Performance of Copper Indium Gallium Selenide (CIGS) Based Photovoltaic Thermal

Abstract: Abstract. This paper deals with the efficiency improvement of Copper Indium Gallium Selenide (CIGS) Photovoltaic (PV) and also solar thermal collector. Photovoltaic thermal (PV/T) can improve overall efficiency for PV and also solve the problem of limited roof space at urban area. Objective of this study is to clarify the effect of mass flow rate on the efficiency of the PV/T system. A CIGS solar cell is used with rated output power 65 W and 1.18 m 2 of area. 4 set of experiments were carried out, which were: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The performance of PV/T can be effected by the packing factor of the system. As stated by Vats et.al [13], the increase of packing factor is not always proportional with the system efficiency. An optimal packing factor value is crucial because higher packing factor value will increase the temperature of PV module while low packing factor value will reduce the solar radiation absorber area.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The performance of PV/T can be effected by the packing factor of the system. As stated by Vats et.al [13], the increase of packing factor is not always proportional with the system efficiency. An optimal packing factor value is crucial because higher packing factor value will increase the temperature of PV module while low packing factor value will reduce the solar radiation absorber area.…”
Section: Introductionmentioning
confidence: 88%
“…In previous studies, effect of mass flow rate has been investigated in the range of 0.01kg/s-0.30kg/s [12]. A study on unglazed PV/T for different mass flow rate has been carried out by Zulkepli et.al [13] and it was reported that the highest thermal efficiency achieved at the mass flow rate of 0.12 kg/s. CIGS thin film is one of the second generation of PVs and it is thin and very light weight [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, such capacity is rated at Standard Test Conditions (STC) and the actual power generation will be less than that as factors including irradiance and ambient temperature vary from day to day. Temperature is one of the major factors that contributes up to 17.5% efficiency loss in polycrystalline silicon PV module when the panel temperature exceeds 60°C [3], [4], [5]. Thus, there are many methods studied by various researchers to cool down the PV panels.…”
Section: Introductionmentioning
confidence: 99%